Study on the regulation of sludge dewatering by hydrophobically associating cationic polyacrylamide coupled with framework materials. (February 2022) - Feng, Xin; Wan, Junjie; Deng, Jinchuan; Yue, Xiu; Yang, Yulong; He, Zhanlong; Fang, Xiaohui; Chen, Tulan; Li, Shumin; Lu, Jiankai; Long, Yaoguo
Abstract: To further improve the performance of sludge dewatering, this study used the UV-light-initiated aqueous micellar polymerization method to obtain hydrophobic associating cationic polyacrylamide (HACPAM) as a flocculant and coupled it with quartz sand and fly ash to investigate sludge flocculation and dewatering. The results show that the flocculation of HACPAM is interfered with by the framework material quartz sand and fly ash, which leads to significant changes in the sludge floc particle size, capillary suction time (CST), settlement performance and other indicators. This is the result of the coupling between HACPAM and the framework materials. The larger the molecular weight of HACPAM, the larger the particle size of the sludge flocs is, and the better the dehydration performance. The dosage of 7.5784 kg/ton (T) dry solids (DS) is the optimum dosage level when the sludge dewatering performance is the best. It is represented by the largest sludge floc size (2280 μm), the highest removal free water content (90.9%) and the inflection point of CST change (59.3 s). When HACPAM is coupled with quartz sand and fly ash flocculated sludge, different characteristics of dewatering performance are showed. Both low-dose HACPAM 3 coupled with fly ash and high-dose HACPAM 3 coupled with quartz sand can achieve better dehydration effects, but the former has more advantages than the latter. The 3D scanning structure explains why HACPAM 3 is more suitable for coupling fly ash to improve the dewatering performance of sludge. In addition, the mechanism is also discussed. Graphical abstract: Unlabelled Image Highlights: The larger the molecular weight of HACPAM, the larger the particle size of the sludge flocs. A coupling effect occurred between HACPAM and quartz sand and fly ash, different characteristics were exhibited. Low-dose HACPAM 3 coupled with fly ash and high-dose HACPAM 3 coupled with quartz sand can achieve better effects. The 3D scanning structure explains why HACPAM 3 is more suitable for coupling fly ash to improve the performance.